Determinan tingkat keberlanjutan partisipasi pada program kampung KB di Desa Cau Belayu, provinsi Bali - Asriningsih, Ni Luh Putu Withari; Marhaeni, A.A Istri Ngurah (ARKA INSTITUTE, 2024)
The purpose of this study was to analyze simultaneous and partial effects of education, income, number of children, implementation Catur Guru teachings, and understanding of the Balinese Krama KB concept on the Level Sustainability KB Participation in the KB Village Program in Cau Belayu Village. Also, to analyze the role of understanding the Balinese Krama KB concept in moderating the implementation of Catur Guru teachings on the level of sustainability of KB participation in the KB Village Program in Cau Belayu Village. This study used a quantitative method with sample of 81 people. Data analysis was using logistic regression and moderation analysis. The results showed education, income, number of children, implementation Catur Guru teachings, and understanding of the Balinese Krama KB concept simultaneously had a significant effect on the sustainability of KB participation. Partially, education, number of children, and implementation Catur Guru teachings had positive and significant effect, while income and understanding the Balinese Krama KB concept had negative effect. It can be concluded that the five variables are able to explain the factors that influence KB participants in determining the decision to continue using contraception or not, the rest explained or influenced by variables not included in the study.